2018
DOI: 10.1126/science.aao0218
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “The whole-soil carbon flux in response to warming”

Abstract: In a compelling study, Hicks Pries et al . (Reports, 31 March 2017, p. 1420) showed that 4°C warming enhanced soil CO 2 production in the 1-meter soil profile, with all soil depths displaying similar temperature sensitivity (Q 10 ). We argue that some caveats can be identified in their experimental approach and analysis, and that these critically undermine their conclusions and hence their claim that the strength of feedback between the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Depending on soil saturation (or E a ), increasing temperature from 5 to 35°C could dampen respiration rates by approximately 60% due to reduced O 2 dissolution and increased hydraulic resistance against O 2 flux from the water–air interface to the reactive sites as temperature rises. This is consistent with experimental results that reducing O 2 supply substantially reduced respiration [52]; it is also corroborated by the results of a whole soil profile experiment where E a in the subsoil was greater than that in the topsoil [66,67]. While biological factors such as differences in SOC quality and microbial community composition between the top- and sub-soils are also likely to be important [68,69], O 2 dissolution and diffusion are critical factors because the subsoil is more saturated, and the preferential consumption of O 2 by roots and microbes in the topsoil limits O 2 diffusion to reactive sites in the subsoil.…”
Section: Resultssupporting
confidence: 90%
“…Depending on soil saturation (or E a ), increasing temperature from 5 to 35°C could dampen respiration rates by approximately 60% due to reduced O 2 dissolution and increased hydraulic resistance against O 2 flux from the water–air interface to the reactive sites as temperature rises. This is consistent with experimental results that reducing O 2 supply substantially reduced respiration [52]; it is also corroborated by the results of a whole soil profile experiment where E a in the subsoil was greater than that in the topsoil [66,67]. While biological factors such as differences in SOC quality and microbial community composition between the top- and sub-soils are also likely to be important [68,69], O 2 dissolution and diffusion are critical factors because the subsoil is more saturated, and the preferential consumption of O 2 by roots and microbes in the topsoil limits O 2 diffusion to reactive sites in the subsoil.…”
Section: Resultssupporting
confidence: 90%
“…4, the variation extent of soil temperature under NT and ST was smaller compared with CT at both two time points, thus indicating a poor ability to regulate soil temperature under CT. The high temperature in the 20-25 cm soil layer under NT and ST treatments, which may be partially attributed to lagging effect of soil temperature conduction and straw mulching 51,52 . Meanwhile, the soil temperature under NT was generally higher than that under CT and ST at 10 o' clock ( Fig.…”
Section: Effects Of Different Tillage Treatments On Soil Properties mentioning
confidence: 97%
“…This phenomenon could be explained by the energy exchanges between land and atmosphere; Shallow soil layers are more affected by the daily changes of solar radiation, leading to stronger fluctuations. Hence, the deeper layer are also suggested to paid more attention as the temperatures of deep soil layers can reflect long‐term anomalies in the surface heat budget, which can be used to predict climate change (Yang and Zhang, 2016; Xiao et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing number of studies have shown strong interest in deep soil layers, as the temperatures of deep soil layers can reflect long‐term anomalies in the surface heat budget (Hu and Feng, 2003; Knight et al ., 2018). Thus, there is added value in studying the soil temperature changes, and many studies have shown a strong correlation between soil temperature and climate change predictability (Yang and Zhang, 2016; Xiao et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%